SUMBANGAN USAHA TERNAK KAMBING DAN USAHA TANAMAN KAKAO TERHADAP PENDAPATAN PETANI DI KABUPATEN MANGGARAI TIMUR - Melkianus D. S. Randu (Politeknik Pertanian Negeri Kupang, 2009)
The aim of this research was to know levels of farmers income contributed by goat management and cacao crop production; and also factors effecting farmers income from goat management and cacao crop production. Survey method was applied in this research. The data were processed and analysed statistically and economically. The results indicate thatÂ 1) total income of a respondent in East Manggarai District through goat management and cacao crop in 2008 was Rp.3,915,796.- in which Rp. 992,753.- (25.35 %) contributed by the first and Rp. 2,923,043.- (74.65 %) by the latter; 2) factors effecting farmers income from goat management were number of livestock sold, and number of livestock slaughtered (R2 = 0,885); 3) factors effecting farmers income from cacao crop production were area of cacao crop production, and number of production of cacao crop (R2 = 0,953).Keywords: Income, Goat, Cacao